Mathematical and Computational and Modeling for Leprosy’s Dynamics - Dias, Claudia Mazza; Pastore, Dayse Haime; De Souza Filho, Erito Marques (REVISTA CEREUS, 2019)
This paper deals with the mathematical modeling of leprosy, an infectious and contagious disease considered neglected. A compartmental model is analyzed in the investigation of the dispersion of leprosy in a population in order to predict the transmission of new patients and allowing different groups of individuals to be analyzed in the face of exposure and infection, seeking the impact on the understanding of transmission and planning of disease control strategies.